PROBLEMS OF RESERVE DEVELOPMENT PROJECTS IN COMMERCIAL BANKS - Daminova Sardorxon Baxromovna (Journals Park Publishing, 2025)
The article considers the problem of the personnel reserve work in a bank. The first lines provide an analysis of theoretical sources on the issue of the personnel reserve. Interest in the problems of forming a personnel reserve is still relevant. The personnel reserve is presented in any company that cares about solving the problems of training the quality of personnel competencies. The risks of hiring employees are very high. However, the personnel reserve does not always solve the problems of personnel continuity. In Russian companies, an employee often spends decades in the personnel reserve, enough funds are spent on him to prepare for management, but he may never take a leadership position. There is an understanding that the personnel reserve is needed not only for management structures, it is necessary to close emerging vacancies quickly for less losses. The article considers the situation of the need to form a personnel reserve of a bank. An analysis of the organization of work without a personnel reserve is carried out. An attempt is made to analyze the costs of personnel training without a personnel reserve system. The line of career development of employees of settlement and cash services in the bank is shown. Horizontal movements are considered when an employee moves from one department to another. The author shows that the first steps have been taken in the formation of a personnel reserve. The bank is ready to work in this direction to solve important personnel problems.
Keywords: Personnel reserve; personnel risks; training formation; personnel reserve analysis; efficiency assessment; theoretical analysis of the personnel reserve.